A new species of Sphelodon Townes (Hymenoptera: Ichneumonidae: Banchinae) from Colombia - Herrera-Florez, Andres Fabian (Zootaxa, 2017)
The genus Sphelodon Townes has 13 described species, nine species from the Neotropical region, three species from the Nearctic region and one (Sphelodon phoxopteridis) that occurs in both regions. A new species, Sphelodon antioquensis sp. n. is described here. This is the first record of Sphelodon for Colombia. A key to Sphelodon species occurring in the Neotropical Region is provided.